Моделювання ризиків виконання програм розвитку озброєння та військової техніки в умовах оборонної реформи в Україні - Остапенко, О.П. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The article presents a model for risk assessment of default program of weapons and military equipment in the Armed Forces of Ukraine, developed on the basis of a method of expert estimations and then applying the dispersion method quantitative risk assessment. This model can be used in the development of an integrated risk management system in the Armed Forces of Ukraine provided the Strategic defense bulletin.